Academic Failure: Unspoken Experiences by International Postgraduate Students in a Malaysian University - Jasvir Kaur Nachatar Singh (IAFOR Journal of Education, 2020)
Malaysia aspires to become a regional and international hub of higher education through an international student mobility initiative. Existing scholarly work on international students is skewed towards understanding the general challenges faced by international students, but limited work has been conducted in exploring the impact of severe supervision challenges on international postgraduate students’ experiences in a Malaysian research university. Hence, this paper explores the evidence of academic failure experienced by international postgraduate students by drawing on semi-structured interviews with 33 international postgraduate students. Academic failure experiences were faced by international postgraduate students as a result of two major challenges: supervision issues, and faculty mismanagement. The experience of academic failure has impacted the students’ enthusiasm, motivation and inspiration in progressing in their research work and has also impacted them psychologically. The implications for developing significant and profound strategies to assist international postgraduate students in achieving positive educational outcomes are also discussed.